Problemas sanitarios en Eucalyptus benthamii agravados por la sequía = Health problems and drought affect the performance of Eucalyptus benthamii - Ramos, Sergio Orlando; Harrand, Leonel; Oberschelp, Gustavo Pedro Javier (Facultad de Ciencias Forestales, Universidad Nacional de Misiones (UNaM), 2025)
Abstract Eucalyptus benthamii has been introduced to Argentina due to its high tolerance to frost damage. However, health problems were reported. The phytosanitary status of a 19-month old progeny trial located in Concordia was assessed. Chlorosis by eucalypts bronze Thaumastocoris peregrinus bug and pau preto-Botryosphaeria was determined. Both variables increased their severity with diameter. There was no effect of the families tested. Frequencies for chlorosis-bronze bug were 0,6% no symptoms; 9,4% low; 54,8% moderate and 36,2% high. Frequencies for pau preto-Botryosphaeria were 7,4% no symptoms; 15,9% low; 53,8% moderate and 22,9% high. Both health problems were aggravated by the 2020-23 drought.